Deep Venous Thrombosis in Patients with Erythema Nodosum Leprosum in the Use of Thalidomide and Systemic Corticosteroid in Reference Service in Belo Horizonte, Minas Gerais. (19th June 2019) - Pôrto, Luiz Alberto Bomjardim; Grossi, Maria Aparecida de Faria; Alecrim, Edilamar Silva de; Xavier, Marcus Henrique de Souza Brito; Paiva e Silva, Frederico; Pires, Amalia Sathler; Silva, Fabianny Sanglard da; Lyon, Sandra
Abstract : Introduction . Erythema nodosum leprosum (ENL) is a type of lepra reaction treated with corticosteroids and thalidomide, but this association increases the risk of deep venous thrombosis (DVT). Objective . To report cases of ENL with DVT in the use of thalidomide/corticosteroid associated. Methodology . The study was conducted between December 2015 and December 2016 at the Eduardo de Menezes Hospital (HEM-FHEMIG). Results . A clinical case series of 16 patients, eight from HEM-FHEMIG and eight from the literature. DVT occurred on 4 continents, mainly in adults and men. All patients were multibacillary; four people had pulmonary embolism (PE); there were 11 unilateral and five bilateral DVT cases; 12 cases were proximal, two distal, and two unspecified. Pharmacological thromboprophylaxis was used on two individuals. Outcome after DVT, 14 patients improved, one had sequelae, and one died. Discussion . DVT increased in association with thalidomide/corticosteroid in multiple myeloma, but this complication is poorly described in ENL. In proximal DVT, there was a greater risk of PE and sequelae venous insufficiency. After DVT, start anticoagulation. ASA 100mg/day as prophylaxis for DVT in case of this drug association in ENL is recommended. Conclusion . The article illustrates the incidence increase of DVT because of the thalidomide/corticosteroid combination in ENL. When this association is necessary, use ASA 100mg/day as prophylaxis.